The Practice of Mindful Communication Brings the Strong Effect on Spiritual Intelligence of School Students - Candra Kusuma; Vike Aprilianin Marwintaria Saputri; Rini Kasrah; Ine Yudhawati; Sidartha Adi Gautama (Journal of Communication, Religious, and Social Sciences (JoCRSS), 2023)
This study aims to describe the influence analysis of students' mindful communication abilities on the spiritual intelligence of Triratna High School students in West Jakarta. Mindful communication ability is the communication ability that is adequately conveyed by being aware of aspects of language and communication ethics. Character is formed due to an understanding of the three relationships that every human being must experience. Spiritual intelligence is the foundation for intellectual and emotional intelligence to function effectively. This study used a descriptive approach and a quantitative regression method using two instruments to measure mindful communication's effect on students' mental intelligence at Triratna school, West Jakarta. The results of this study indicate that there is a positive relationship between mindful communication and cognitive intelligence. The results of this study contain implications that mindful communication has an essential role for students.